1996
DOI: 10.1021/jp952415q
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Two-Photon Ionization Spectroscopy of the Aniline Dimer

Abstract: The resonance two-photon ionization (R2PI) spectra of the jet-cooled aniline dimers (An-d 0 ) 2 , (An-d 5 ) 2 , and (An-d 7 ) 2 have been recorded; the first 225 cm -1 region above the (An-d 0 ) 2 origin was also reproduced by fluorescence excitation spectroscopy. Relatively sharp structure near the origin of the local excited state is attributed to intermolecular modes, perhaps of multiple conformers. Broader features at higher energies are assigned to symmetric ring modes coupled to an underlying excimer sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…30,31,60 These two features were attributed to different isomers, and the presence of at least two different isomers was confirmed in subsequent two-color hole-burning spectra. 61 Similar studies using R2PI and zero-kinetic energy (ZEKE) spectroscopy have been reported on substituted benzene dimers, including dimers of fluorobenzene, [62][63][64][65][66][67][68][69] chlorobenzene, 58,70 phenol, aniline, [71][72][73][74] and others. 39,75 Building upon the seminal studies of Bernstein and others, Musgrave and Wright recently reported R2PI spectra of mass-selected toluene homoclusters (Tol) n up to n = 8, 60 and parafluorotoluene clusters (pfTol) n up to n = 11.…”
Section: Introductionsupporting
confidence: 53%
“…30,31,60 These two features were attributed to different isomers, and the presence of at least two different isomers was confirmed in subsequent two-color hole-burning spectra. 61 Similar studies using R2PI and zero-kinetic energy (ZEKE) spectroscopy have been reported on substituted benzene dimers, including dimers of fluorobenzene, [62][63][64][65][66][67][68][69] chlorobenzene, 58,70 phenol, aniline, [71][72][73][74] and others. 39,75 Building upon the seminal studies of Bernstein and others, Musgrave and Wright recently reported R2PI spectra of mass-selected toluene homoclusters (Tol) n up to n = 8, 60 and parafluorotoluene clusters (pfTol) n up to n = 11.…”
Section: Introductionsupporting
confidence: 53%
“…The obtained results are consistent with recent spectroscopic studies in terms of binding energy and geometrical conformation of the dimer. 39,40 Since the 2:1 molar ratio is observed for aniline in the experimental part of the study, the dimer of two guest molecules is introduced into the cavity of γ-CD for a more proper comparison ( Figure 6). The various locations and the complexation energy (E comp ) for the lowest energy orientations are calculated as…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…The aniline dimer and trimer structures were investigated in the ground and excited states previously. [21][22][23] The N-H site in the amino group of aniline can form a hydrogen bond with a lone pair of the nitrogen atom of another aniline or with the p electrons of its benzene ring. The neutral structure of the aniline dimer shows relative stability for both conformers: the stacked complexes with a N-p type hydrogen bond and N-HÁ Á ÁN bonding with head-to-tail orientation.…”
Section: Introductionmentioning
confidence: 99%